CROSS SELLING AND ECOTOURISM DEVELOPMENT: A STUDY ON THE MARKETING DYNAMICS - Sofi Cherian and L. Prema (REVIEW OF SOCIAL SCIENCES, 2014)
Ecotourism is viewed as the fastest grooming industry in International tourism scenario. Ecological tourism helps the visitors to an educative experience of diverse milieu, ambience causing minimum damages to mother mature. It is since more than a decade now, we have started developing eco-tourism projects in Kerala. But the contribution of this sector towards the total output of the industry (ecotourism) is still negligible. The strategies which we are resorting now could be one of the reasons for this reduced growth. Considering the wide bio-diversity of Kerala, eco-tourism as a product has a lot of opportunities still left to be explored in its fullest extent. There is a need for developing novel marketing practices and strategies for promoting the Eco-Tourism products available in Kerala. The present study was focus on the attention to develop innovative strategy i.e. cross selling of eco-tourism products in Kerala for its survival and development. Cross-selling is a practice of selling an additional products or service to tourist with a view to develop ecotourism industry,reduce the per tourist cost of operations and provide more satisfaction and value to the tourist. Visitor retention is likely to be a key strategy in the future arena which can be depend on innovative strategy i.e. cross selling. Cross-selling opportunities can accrue to the tourist, the efficiency and leverage that result from using a single tourism destination for multiple tourism products and further promote cross-selling to main stream business strategy.